Identity as a means of subordination: political-anthropological research into the history of haciendas in Chile’s central valley - Danilo Petrovich Jorquera, Daniel Flores Cáceres, Daniel González Hernández,; Olga Carrillo Mardones, Andrés Rojas-Bottner, (Opción, 2019)
This article provides a political and anthropological interpretation of the pre-modern tributes and gifts used by Chile‘s haciendas to hire workers. It then goes on to explain how this system was transformed into an ideology and world view for the landholding class and was subsequently adopted nationwide. As well as being a means of exploitation, it is suggested that haciendas also introduced the idea (and created the identity) of a population made up of their subjects. It is claimed that the latter were both unproductive and lacking identity and could only become productive and cultural beings through subordination to landowners